The Historical Development of the Mission Preparation School in Makah Al-Mukarramah (1355-1373 AH / 1936-1953 AD) - Dada, Sahar Ali (Journal of Tikrit University for Humanities, 2022)
The study showed the interest of the founder of this state, His Majesty King Abdul Aziz bin Abdul Rahman Al Saud, in the educational process in general, and in the Hijaz region in particular. It also showed the role of the Directorate of Public Education in promoting the educational process throughout the Kingdom of Saudi Arabia, through the establishment of schools in various regions, and delegations were established in each of the regions affiliated to it, to follow up the progress of the educational process there.The study also included giving a clear picture of the Mission Preparation School, in terms of its importance, goal and purpose of its establishment, and traced the historical development of the Mission Preparation School from 1355-1373 AH / 1936-1953 AD.The Scholarship Preparation School is the basic nucleus in organizing foreign scholarships by preparing Saudi students to continue their higher education in foreign universities. Over the years, it has taken over the years to work on developing admission mechanisms, academic courses, examination system, and others, and these scholarships are the basic building block for renaissance. The civilization witnessed by the Kingdom of Saudi Arabia at the hands of the founder, His Majesty King Abdul Aziz, where the missions contributed to the process of development and progress in our country, the Kingdom of Saudi Arabia.